2008
DOI: 10.1002/dvdy.21529
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of the decoy bone morphogenetic protein receptor BAMBI in the developing avian face

Abstract: Here, we examine the expression and regulation of the gene BAMBI, a kinase-deficient decoy receptor capable of interacting with type I bone morphogenetic protein (BMP) receptors in avian embryos. Initially, expression was limited to the endoderm during neurula and pharyngula stages. From embryonic day 3.5 (stage 20) and onward, BAMBI expression almost perfectly overlapped with known expression patterns for BMP4, particularly in the face and limbs. We performed bead implant experiments in the face to see which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…Several BMPs (BMP2, BMP4, BMP7) and BMP antagonists (NOGGIN, BAMBI) are expressed in the epithelium and mesenchyme of the frontonasal mass, in some cases overlapping with TBX22 and other times in complementary domains (Francis-West et al, 1994;Ashique et al, 2002a;Foppiano et al, 2007;Higashihori et al, 2008). From these data, it is not possible to predict whether increased or decreased levels of BMP signaling affect TBX22 expression.…”
Section: Regulation Of Tbx22 By Bmpsmentioning
confidence: 99%
“…Several BMPs (BMP2, BMP4, BMP7) and BMP antagonists (NOGGIN, BAMBI) are expressed in the epithelium and mesenchyme of the frontonasal mass, in some cases overlapping with TBX22 and other times in complementary domains (Francis-West et al, 1994;Ashique et al, 2002a;Foppiano et al, 2007;Higashihori et al, 2008). From these data, it is not possible to predict whether increased or decreased levels of BMP signaling affect TBX22 expression.…”
Section: Regulation Of Tbx22 By Bmpsmentioning
confidence: 99%
“…BAMBI is incorporated into complexes with TGF-β/BMP/activin type-2 receptors (TGFR2/BMPR2) and, as a pseudoreceptor, antagonizes all TGF-β/BMP and activin signaling. 10, 11 BAMBI is tightly co-expressed with BMP4 during embryonic development in zebrafish, Xenopus , birds and mice 10, 12, 13, 14 through TGF-β 15 and Wnt signaling. 16 …”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that Xenopus BAMBI functions as a general antagonist for TGF-␤ family members (TGF-␤, activin, and BMP) by acting as a pseudoreceptor to block the interaction of signaling type I and type II receptors (18). BAMBI is tightly coexpressed with BMP during development in Xenopus, mouse, and zebrafish (18,20,21,23,24), and its expression is induced by BMP4 (18, 24), TGF-␤ (25), ␤-catenin (17), lipopolysaccharide (26), and retinoic acid (23).Several studies have suggested that BAMBI is involved in pathogenesis of various kinds of human diseases. The human BAMBI, initially named as nma, is down-regulated in metastatic melanoma cell lines (22), and has been implicated to promote cell growth and invasion in human gastric carcinoma cell lines (27).…”
mentioning
confidence: 99%
“…It has been documented that Xenopus BAMBI functions as a general antagonist for TGF-␤ family members (TGF-␤, activin, and BMP) by acting as a pseudoreceptor to block the interaction of signaling type I and type II receptors (18). BAMBI is tightly coexpressed with BMP during development in Xenopus, mouse, and zebrafish (18,20,21,23,24), and its expression is induced by BMP4 (18, 24), TGF-␤ (25), ␤-catenin (17), lipopolysaccharide (26), and retinoic acid (23).…”
mentioning
confidence: 99%